2020
DOI: 10.46831/jpas.v1i1.5
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and outcome of complicated appendicitis in toddlers and pre-schoolers

Abstract: Background: Acute appendicitis is a frequent indication of emergency abdominal surgery in the pediatric population. In younger children, especially toddlers, and preschoolers, the presentation is comparatively late resulting in complicated appendicitis. This study was done to determine the frequency and outcome of complicated appendicitis in toddlers and preschoolers. Methods: This is a cross-sectional study done at the Department of Pediatric Surgery, Lady Reading Hospital Peshawar, during August 2018 and Feb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…In another study by Chung et al, the authors reported that 60% of cases had acute appendicitis, 17% had perforated appendix, and 23% had appendicular abscess [ 20 ]. A recent study by Khan et al investigated complicated appendicitis in toddlers and found perforated appendicitis with a localized abscess in 68 patients, gangrenous appendicitis in four patients, generalized peritonitis in 24 patients, and appendicular mass in 12 patients [ 21 ]. Our result was in some agreement with the previously mentioned researchers.…”
Section: Discussionmentioning
confidence: 99%
“…In another study by Chung et al, the authors reported that 60% of cases had acute appendicitis, 17% had perforated appendix, and 23% had appendicular abscess [ 20 ]. A recent study by Khan et al investigated complicated appendicitis in toddlers and found perforated appendicitis with a localized abscess in 68 patients, gangrenous appendicitis in four patients, generalized peritonitis in 24 patients, and appendicular mass in 12 patients [ 21 ]. Our result was in some agreement with the previously mentioned researchers.…”
Section: Discussionmentioning
confidence: 99%